José María Lacarra, an archivist in the Spanish Civil War (1936-1939) - Pérez Boyero, Enrique (Huarte de San Juan. Geografía e Historia, 2010)
The Nobility Section of the National Historical Archive was founded in 1988 with the aim of preserving the archival funds of the nobility which had been purchased by the State or donated by their owners. The role played by the nobility as holders of office at the head of both State and Church since the late Middle Ages, further developed in Modern and Contemporary times, and their country-wide marital links, led to the contacts and relationships of some of their members with Navarre. The author identifies the documents related to their political, military or religious responsibilities in the old kingdom, but these also derived from the administration of their own properties.